AB0328 SIMILAR EFFICACY OF TOFACITINIB THERAPY IN BIOLOGIC NAIVE AND HAD PRIOR BIOLOGIC USE HISTORY PATIENTS WITH RHEUMATOID ARTHRITIS (OREL REGISTER). (13th June 2020) - Nasonov, E.; Avdeeva, A.; Misiyuk, A.; Satybaldyev, A.; Sorotskaya, V.; Fomina, O.; Babaeva, A.; Lapkina, N.; Lila, A.
Abstract : Objectives: To evaluate the efficacy of tofacitinib therapy (TOFA) in biologic naive and had prior biologic use history patients with rheumatoid arthritis (RA) according to OREL register Methods: Were analyzed the data from Russian national register of patients with RA - OREL treated with TOFA. 138 patients (118 woman, Me;IQR age 55.0 (43.0-63.0) years, disease duration 128.0 (84.0-213.0) months, mean DAS 28 5.5 (4.6-6.2), SDAI 30.5 (21.4-42.9), positive for ACCP (73%)/RF (77%), who were non-responders to MTX at least 15 mg/week and/or other synthetic DMARDs) who received TOFA therapy for more than 1 year were selected for statistical analysis. TOFA used in 26 (18.8%) pts without DMARDs, combination with MTX in 82 (59.4%) pts, leflunomide in 21 (15.2%). Low-dose oral corticosteroids (<10 mg/day prednisone or equivalent) were received by 43 (31.2%) pts. TOFA therapy was started in all pts in dose 5 mg BID per os with dose escalation to 10 mg BID in (86%) pts. Results: The use of TOFA was accompanied by a decrease in the disease activity and the level of acute phase reactants (CRP and ESR) after 12, 24 and 48 weeks of therapy, p<0.05, table 1 . Depending on the previous treatment with biological DMARDs, all patients were divided into two groups: had prior biologic use history pts (group 1) (n=51) and biologic naïve pts (group 2) (n=87), table 1 . Patients of the second group had a higher disease activity and ESR before therapy. The use of TOFA was accompanied by a decrease in the disease activity and the level of acute phase reactants (CRP and ESR) in both groups of patients. By week 48 of treatment, no significant difference between the groups according to the disease activity was detected. In the first and the second group of pts on the 48-th week of therapy remission/low disease activity was achieved on DAS 28 in 51% and 43% (р=0.57), high disease activity on DAS 28 in 12% and 8% (p=0.48). Conclusion: An analysis of the data from the Russian national register of patients with RA demonstrated similar efficacy of TOFA among patients who received and did not receive previous biological therapy. Disclosure of Interests: Evgeny Nasonov Speakers bureau: Lilly, AbbVie, Pfizer, Biocad, R-Pharm, Anastasia Avdeeva: None declared, Anna Misiyuk: None declared, Azamat Satybaldyev: None declared, Valentina Sorotskaya: None declared, Oxana Fomina: None declared, Aida Babaeva: None declared, N Lapkina: None declared, Alexander Lila: None declared